Frequency response of AlN-based solidly mounted resonators under mechanical stress - Clement, M.; Delicado, A.; Olivares, J.; Mirea, T.; Sangrador, J.; Iborra, E. (Sensors and actuators. A. Physical., 2017)
•Sensitivity to strain of AlN-based solidly mounted resonators is investigated.•Two apparatus are fabricated to subject the samples to a controlled strain.•Longitudinal modes are more sensitive to strain than shear modes.•High k2 resonators are more sensitive to strain.•Strain coefficients of the resonant frequency up to −71% per unit strain are achieved. We analyse the performance of solidly mounted bulk acoustic wave resonators under induced mechanical stress to explore their viability as strain sensors. The resonators are made of polycrystalline AlN piezoelectric thin films containing uniformly tilted microcrystals to excite both longitudinal and shear modes. The resonators are grown on top of silicon bars that are fixed at one or two edges using two home-made apparatus specifically designed to induce deformations of several hundreds of microstrains. The induced strain causes frequency shifts of tenths of MHz, yielding strain coefficients of the resonant frequency (SCF) up to −71% per unit strain (−0.71ppm/μe). The influence of the nature of the resonant mode (shear of longitudinal), the electromechanical coupling factor and the operation frequency on the SCF is analysed.